The Teaching and Educational Traditions of the Reformed Church - Judit BOGNÁRNÉ KOCSIS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Hungarian Reformed Church was a so-called „church of schools” for hundreds of years. It means that even in the time between WW. I and WW. II it owned more schools than churches. The number of Reformed schools is significant even today. According to the Educational Act of the Hungarian Reformed Church, the aims and tasks of Reformed schools are clear and among them appears the function of giving equal chances. This function has two main tasks: in one hand it admits socially disadvantaged children and on the other hand it provides those in need with financial aid and support. Several foundations give regular social aid in forms of scholarships and support of higher education and trips, the money is donated by alumni. Sándor Karácsony claims that only Reformed people and communities are able to maintain Reformed schools; people who „are ready to serve and sacrifice”[1] He considers donation to be the only solution as it is written in the Bible. He expects not only adults to do so but Reformed students too. He would like to bring alive an old tradition when every student gave a little amount of their pocket money to other children. This tradition teaches children what charity is, which is necessary for the Reformed to survive. The so-called „particula”-system should also be mentioned among Reformed historical traditions. It helped in supporting talented students by financing their education. Reformed educational traditions evolved in a social environment based on religious moral values. The main task of Reformed pedagogy is to continuously activate divine notions in this continuously changing world. Protestant teachers must do their daily work according to the Gospel of Christ.